2020
DOI: 10.1093/jnen/nlaa137
|View full text |Cite
|
Sign up to set email alerts
|

Somatic Focal Copy Number Gains of Noncoding Regions of Receptor Tyrosine Kinase Genes in Treatment-Resistant Epilepsy

Abstract: Epilepsy is a heterogenous group of disorders defined by recurrent seizure activity due to abnormal synchronized activity of neurons. A growing number of epilepsy cases are believed to be caused by genetic factors and copy number variants (CNV) contribute to up to 5% of epilepsy cases. However, CNVs in epilepsy are usually large deletions or duplications involving multiple neurodevelopmental genes. In patients who underwent seizure focus resection for treatment-resistant epilepsy, whole genome DNA methylation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…Interestingly, Anwar et al identified frequent recurrence of CNVs in PDGFRA gene in a next-generation sequencing-based CNV study of invasive breast cancer patients (Anwar et al 2020 ). PDGFRA CN gain was also detected in intractable epilepsy and high-grade astrocytoma and found to be significantly associated with the treatment and prognosis of the disease (Phillips et al 2013 ; Vasudevaraja et al 2021 ). While the importance of the tumor microenvironment has been increasingly recognized, the complexity of interaction between tumor cells and their microenvironment is becoming evident.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, Anwar et al identified frequent recurrence of CNVs in PDGFRA gene in a next-generation sequencing-based CNV study of invasive breast cancer patients (Anwar et al 2020 ). PDGFRA CN gain was also detected in intractable epilepsy and high-grade astrocytoma and found to be significantly associated with the treatment and prognosis of the disease (Phillips et al 2013 ; Vasudevaraja et al 2021 ). While the importance of the tumor microenvironment has been increasingly recognized, the complexity of interaction between tumor cells and their microenvironment is becoming evident.…”
Section: Introductionmentioning
confidence: 99%
“…This evidence illustrates that mast cell involvement in the immune response to achieve neuroinflammatory regulation has a potential regulatory role in epilepsy. Further, It was reported that EGFR was significantly associated with the risk of epilepsy occurrence ( 48 ), and overexpression of EGFR caused by focal copy number gains was identified in epilepsy ( 49 ). EGFR belongs to the receptor tyrosine kinase family.…”
Section: Discussionmentioning
confidence: 99%
“…PMG is a group of highly heterogeneous and difficult to classify MCD (55, 56). Their description is primarily based on their localization (by MRI; e.g., focal, multifocal, or generalized, unilateral or bilateral symmetric/asymmetric) and correlation with clinical aspects including developmental course, growth anomalies, and dysmorphism, seizure history, family history, and genetic testing of blood for PMG‐associated genes (24). Over 40 genes with germline mutations have so far been linked to PMG types and syndromes, but only very recently also brain somatic events were reported.…”
Section: Brain Somatic 1q Trisomymentioning
confidence: 99%